THE RATIO OF HUMAN AND NATIONAL VALUES IN DIFFERENT SOCIAL INSTITUTIONS - Sargsyan, A. A. (Արդի հոգեբանություն, 2019)
The article is analyzes the results of social surveys conducted to study student’s moral and cultural value systems. The results factually show that the student’s value system has undergone dramatic changes, as a result of multifunctional systems. It is proved that the priority of any social institution is the preservation of national values, the harmony of human and national values, to ensure the conservation and the formation of the Armenian, national characteristics. It is possible if the appropriate social institution of national, cultural, moral and personal values will be transferred to the process of interaction between generations.